The Relationship Between Adolescent Girls' Perception and Breast Self-Examination (BSE) Behavior - Elizar, Elizar; Prihatin, Nova Sumaini; Iswani, Rayana; Rosyita, Rosyita; Rosdiana, Yanti (Universitas Tribhuwana Tunggadewi, 2024)
Breast cancer affects women of all ages after adolescence in every country around the world, and its incidence increases with age. One of the efforts to prevent breast cancer is through early screening, which can be done via breast self-examination (BSE). This study aims to analyze the relationship between adolescent girls' perceptions and their behavior regarding breast self-examination at a vocational high school (SMK) in Lhokseumawe City. This research is an observational study with a cross-sectional design. The study was conducted at a vocational high school in Lhokseumawe City with a sample size of 191 students. The selection of research subjects was done purposively according to predetermined criteria. The chi-square analysis results showed that variables such as adolescents' perceptions of severity, self-efficacy, perceived costs, knowledge, family support, and peer support were significantly related to the practice of BSE among adolescents, with a p-value of 0.05. However, after performing multiple logistic regression tests, only the adolescents' perceptions of costs, knowledge, and family support were simultaneously related to BSE behavior, with a p-value of 0.05. Improving adolescents' perceptions of breast self-examination can influence their behavior. Health promotion efforts through information media and involving family and peers as strategies for disseminating health education to adolescents, using demonstrations and involving teachers, are strategies that can be used.